Economic crisis and innovation: Do regions matter? - Adelheid Holl; Ruth Rama (European Regional Science Association (ERSA), 2015)
There is broad agreement among economists and policy makers that economic growth is nowadays largely driven by the capacity of firms to innovate. The financial and economic crisis that started in late 2007 has had a far reaching impact on countries around the world. Spain has been one of the countries worst affected. As a result, the government has reduced public funding in R&D. At the same time, the continued credit crunch has dramatically worsened the possibilities for financing new ideas and projects. One of the consequences of the economic crisis is that many companies have reduced their innovation-related activities; however, some firms have been more resilient than others and recent studies also show that there are important differences across countries regarding the degree to which the economic crisis has affected firms? innovation investment. It has been argued that national institutional settings and the structural characteristics of national innovation systems have played an important role in shaping how firms have responded to the crisis. However, within a country, regions may also matter. Learning processes underlying innovation are localised and locally embedded, and regional innovation systems (hereafter, RISs) may play a role too. Spain provides an interesting setting for analysing the role of regions, as it is a country with a highly decentralized unitary state with a unique framework of territorial administration. Spanish regions have very diverse economies and also different degrees of fiscal and political autonomy. They vary greatly in terms of their innovation performance as well as regarding their regional innovation and technology policies. Moreover, their responses to the economic crisis in terms of regional policies have not been the same. A focus on regional difference can contribute to a better understanding of the innovation strategies employed by firms during the crisis. To date, we still know very little about regional differences and the degree to which regions have shaped firms' innovation behaviour in response to the economic crisis. Our analysis contributes to this literature by drawing on a large national sample of micro-data for Spanish manufacturing and service sector firms. Our results show that the crisis has discouraged a significant number of firms from engaging in innovation. These have been mainly small firms and occasional R&D performers. Significant regional differences are also found in the degree to which the crisis has affected firms? innovation expenditures, even after controlling for sectoral differences and firms? structural characteristics. The Basque Country stands out in our analysis. Firms with R&D employment in this region show a significantly lower probability of having abandoned innovation activities and a somewhat higher probability of even having increased their innovation effort. This regional effect has been especially important for small and medium sized companies.
Keywords: R1; O3; 330; innovation investment; economic crisis; resilience